Rural tourism development : localism and cultural change - George, E. Wanda, 1943- (Tourism and cultural change., 2009)
Rural tourism represents a merging of perhaps two of the most influential yet contradictory features of modern life. This book links changes at the local, rural community level to broader, more structural considerations of globalization and allows for a deeper, more theoretical consideration of the various features of rural tourism development.